THE EFFECTIVENESS OF SOUTH SUMATRA COFFEE (Coffea arabica L.) EXTRACT CREAM IN BURN WOUND RECOVERY OF MALE WHITE MICE (Mus musculus) - Muhammad Romadhon; Dani Prasetyo (Sanata Dharma University, 2021)
The effectiveness of South Sumatra coffee extract cream in burn wound recovery of white male mice had been analyzed. This research aims to ensure which one between immature and mature coffee bean that was better to recover burn wounds of male white mice after 14-day testing. The prepared concentrations for both coffee beans were 0.1%, 0.2%, and 0.3%. We then figured out that ethanol contained by young and old coffee beans had a recovery effect on burn wounds of male white mice (Mus musculus). Findings indicate that 0.3% of mature coffee beans were more effective in recovering burn wounds of male white mice (Mus musculus), in which the wound recovery percentage was close to that in the positive control (burnazin).